Demokrasi, Islam, dan Etika Publik: Memahami Politik Kewargaan di Indonesia - Billahi, Savran (Studia Islamika, 2025)
This article discusses Robert W. Hefner’s Islam and Citizenship in Indonesia: Democracy and the Quest for an Inclusive Public Ethics (2024), that characterizes the interplay between religious culture and politics in Indonesia not as a single trend, but as a contentious project of nation-making and citizen belonging. The book seeks to address broad questions concerning the role and influence of Indonesian Muslim culture and its social movements, the messages conveyed through Islamic higher education, the social roles of Muslim women, and the impact of electoral democracy on the contested interpretations of Islam in the Indonesian public sphere. The book argues that the relationship between religion and state, and other forms of authority in Indonesia as a process of religionization, which distinguished from Islamization, while also emphasizing Indonesia as a site of agonistic plurality. By dispersive and multi-sectoral approach, the book offers a compelling framework for understanding the complex entanglements between religion, state, and society in shaping Indonesian public ethics.